Valores energéticos do milho e do farelo de soja para aves de diferentes categorias zootécnicas - Oliveira, Evelyn Cristina de (2015)
Providing the appropriate amount of dietary energy is determining to achieve maximum zootechnical performance. To make this possible, the knowledge of the accurate feed energy values is necessary. However, the majority of the studies conducted to determine feed energy levels are conducted with broiler chickens and, posteriorly, these values are extrapolated to other categories and species of birds. This work was conducted with the objective of determining the values of metabolizable energy of maize and soybean meal for different categories and species of birds. We used a total of 450 birds of different categories, being 36 adult Leghorn cocks, with 36 weeks of age; 72 Isa Brown pullets, with 13 weeks of age; 72 Isa Brown laying hens, with 25 weeks of age; 180 Japanese quails (Coturnix japonica) in growth, with 21 days of age; 90 male Coon 500® chicks in growth, with 21 days of age. The experimental design was completely randomized, in 5 x 2 + 1 factorial scheme, comprised of five categories/species (cocks, chicks, hens, pullets and quails) and two test feeds (maize and soybean meal), with 6 replicates each. The test feeds substituted the standard feed in 40% and 30%, respectively, for maize and soybean meal. We determined the dry matter coefficient of metabolizability (DMCM), crude energy coefficient of metabolizability (CECM), apparent metabolizable energy (AME) and the corrected apparent metabolizable energy for nitrogen balance equal to zero (AMEn). The data were submitted to variance analysis and, when significant, compared by the Scott-Knott test at 5% of significance. There was interaction between the different categories/species and the test feeds for DMCM, with higher DMCM occurring, for maize, in pullets, while, for soybean meal, the highest DMCM was occurred for chicks. There was no interaction between categories/species and test feeds for CECM. The highest values of CECM for maize were superior to those found for soybean meal, and the highest values of CECM occurred for cocks, pullets and quails. There was significant interaction between categories/species and test feeds for AME and AMEn. For maize, the highest values of AME and AMEn were found for cocks, pullets and quails. For soybean meal, the highest values of AME were determined for chicks, cocks and quails and the highest values of AMEn were found for quails. We concluded that more studies are necessary to determine feed energy values, especially for different species and categories of birds.